Comparisons between the squash bug egg parasitoids Ooencyrtus anasae and O. sp. (Hymenoptera: Encyrtidae): development, survival,and sex ratio in relation to temperature - Tracy, J. L.; Nechols, James R. (My University, 2013)
Laboratory investigations of the gregarious squash bug egg parasitoids Ooencyrtus anasae and O. n. sp. near anasae (O. sp.) were conducted at 20.8, 23.0, and 26.6°C. In both species, total developmental periods (egg to eclosed adult) were inversely related to temperature. Temperature had no significant influence on survivorship, progeny production, or sex ratio. At each temperature, O. anasae developed and emerged about a day earlier and produced a significantly higher percentage of female progeny (77%) than did O. sp. (60%). Both parasitoids deposited an average of three (2-7) progeny per host. However, O. anasae consistently deposited more female eggs per host than did O. sp. Proportion of females produced per host by O. anasae tended to increase directly with number of hosts parasitized, but no such relationship was observed in O. sp. Total preimaginal survivorship in both parasitoids was about 89%. In O. sp., male progeny that developed without females emerged about a day later at all temperatures and had a lower pharate adult survivorship than did males that developed in hosts with female siblings.
Citation: Tracy, J. L., and J. R. Nechols. 1987. “Comparisons Between the Squash Bug Egg Parasitoids Ooencyrtus Anasae and O. Sp. (Hymenoptera: Encyrtidae): Development, Survival, and Sex Ratio in Relation to Temperature.” Environmental Entomology 16 (6): 1324–29. https://doi.org/10.1093/ee/16.6.1324.
Keywords: Insecta; Anasa tristis; Gregarious parasitoids; Biological control; Squash bug